The magnocellular mediodorsal thalamus is necessary for memory acquisition, but not retrieval. - Mitchell, A; Gaffan, D (2008)
Damage to the magnocellular mediodorsal thalamic nucleus (MDmc) in the human brain is associated with both retrograde and anterograde amnesia. In the present study we made selective neurotoxic MDmc lesions in rhesus monkeys and compared the effects of these lesions on memory acquisition and retrieval. Monkeys learned 300 unique scene discriminations preoperatively and retention was assessed in a one-trial preoperative retrieval test. Bilateral neurotoxic lesions of the MDmc, produced by 10 x 1 microl injections of a mixture of ibotenate and NMDA did not affect performance in the postoperative one-trial retrieval test. In contrast, new postoperative learning of a further 100 novel scene discriminations was substantially impaired. Thus, MDmc is required for new learning of scene discriminations but not for their retention and retrieval. This finding is the first evidence that MDmc plays a specific role in memory acquisition.